Kinetics and mechanism of the reduction of n-(2-hydroxyethyl)ethylenediaminetriacetatoiron(III) complex by thioglycol in bicarbonate buffer medium - U. Nkole, I; R. Osunkwo, C; D. Onu, A; D. Onu, O (International Journal of Advanced Chemistry, 2018)
The kinetics and mechanism of reduction of N-(2-hydroxyethyl) ethylenediaminetriacetatoiron (III) complex (hereafter [Fe(III)HEDTAOH2]) by thioglycol (hereafter RSH) has been studied spectrophotometrically in a bicarbonate buffer medium. The study was carried out under pseudo-first order conditions of an excess of thioglycol concentration at 28 Â± 1â„ƒ, I = 0.44 mol dm-3 (KNO3) and Î»max = 490 nm. The reaction is first order in [Fe(III)HEDTAOH2] and half order in [RSH] and a stoichiometric mole ratio of [Fe(III)HEDTAOH2]: RSH is 2:1. Reaction rates increased with increase in ionic strength (I) and dielectric constant (D) of the reaction medium of the reaction. The reaction displayed positive primary salt effect, which suggests the composition of activated complex are likely charged reactants ions. Test for possibility of an intermediate complex formation shows negative as Michaelis-Menten plot was linear with very negligible intercept. Based on the findings, outer-sphere mechanism is proposed for the reaction. The experimental rate law obtained is; - = k2 [Fe(III)HEDTAOH2][RSH]Â½Â Â Â